Hunan Traditional Folk Song Teaching Curriculum Setting in China - Liangyin , Lyu; Nanongkham, Priwan (Journal of Roi Kaensarn Academi, 2024)
As far as the present situation is concerned, most colleges and universities (referring to conservatories and comprehensive colleges and universities with vocal art majors) offer courses on Hunan folk songs only for students specialising in ethnic vocal music, while other vocal majors rarely have courses on Hunan folk songs. In the case of American vocal performance majors, for example, the problem of over-westernisation has not yet been alleviated, either in terms of theoretical elaboration or in terms of practical performance. This situation has also caused some of the American voice students to know that the "Slender Men on the Volga" will sing collectively when they are working collectively, but they do not know that the boatmen in Hunan have the custom of singing the "horn". As we all know, colleges and universities have the mission of "inheriting and promoting Chinese culture", but the problem of excessive westernisation of existing vocal music teaching is simply unable to make this goal a reality. In view of this problem, the viewpoint of this paper is: not only should the theory and practice of Hunan folk songs be offered to students majoring in ethnic singing, but also to students majoring in other vocal disciplines such as American singing, opera performance and popular singing.